Complement system activation in obstructive sleep apnea. (1st March 2018) - Horvath, Peter; Tarnoki, David L.; Tarnoki, Adam D.; Karlinger, Kinga; Lazar, Zsofia; Losonczy, Gyorgy; Kunos, Laszlo; Bikov, Andras
Summary: The complement system may play a role in the systemic inflammation characterising obstructive sleep apnea; however, this has not been investigated before. We aimed to study the involvement of effector complement elements in obstructive sleep apnea, namely C3a, C5a and SC5b‐9. Venous blood was collected in 50 patients with obstructive sleep apnea and 26 control subjects in the evening and the following morning. Plasma complement proteins were analysed with ELISA. Complement factor levels were compared between the two groups and correlated with clinical variables. Plasma C3a concentration was elevated in obstructive sleep apnea both in the evening (84.1 [0–338.5] ng ml −1 ) and in the morning (85.5 [0–247.8] ng ml −1 ) compared with controls (30.3 [0–176.8] ng ml −1 and 36.3 [0–167.1] ng ml −1, evening and morning, respectively, both p  < 0.05). On the contrary, C5a and SC5b‐9 levels were comparable between patients and controls at each time point ( p  > 0.05). There was no change in complement factors from evening to morning in either group ( p  > 0.05), except for C5a that decreased from evening to morning in obstructive sleep apnea (from 11.6 [1.6–47.4] ng ml −1 to 9.3 [0–46.4] ng ml −1, p  = 0.01). Elevated C3a levels were directly related to obstructive sleep apnea severity, and were significantly associated with male gender, weight, body mass index, hypertension, high C‐reactive protein and low high‐density lipoprotein cholesterol ( p  < 0.05). The complement system is activated in obstructive sleep apnea, which is correlated with disease severity. Our findings highlight the potential role of complement system in the pathophysiology of obstructive sleep apnea, thus facilitating further research.